2017
DOI: 10.3892/etm.2017.5597
|View full text |Cite
|
Sign up to set email alerts
|

Tubeimoside I attenuates inflammation and oxidative damage in a mice model of PM2.5‑induced pulmonary injury

Abstract: Abstract. In the present study, the effects of tubeimoside I (TBMS1) on particulate matter <2.5 µm in diameter (PM 2.5 )-induced pulmonary injury and its mechanisms of action were investigated. Male BALB/c mice were randomly assigned into five groups (n=10/group): Control, PM 2.5 , PM 2.5 + TBMS1 45 mg/kg, PM 2.5 + TBMS1 90 mg/kg and PM 2.5 + TBMS1 180 mg/kg. The dose of the PM 2.5 suspension administered to the mice was 40 mg/kg via nasal instillation. The PM 2.5 + TBMS1 groups received TBMS1 daily orally for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Although some animal model experimental studies conducted sporadically for respiratory diseases induced by PM have demonstrated the mechanisms and effectiveness of herbal medicine [17][18][19][20]; however, we did not reach a conclusion on the herbal medicine, mechanism, regimen, and outcome appropriate for research on lung disease induced by PM. Therefore, there is an increasing need to review and verify the mechanisms and effectiveness of various herbal medicines for the treatment of respiratory symptoms.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…Although some animal model experimental studies conducted sporadically for respiratory diseases induced by PM have demonstrated the mechanisms and effectiveness of herbal medicine [17][18][19][20]; however, we did not reach a conclusion on the herbal medicine, mechanism, regimen, and outcome appropriate for research on lung disease induced by PM. Therefore, there is an increasing need to review and verify the mechanisms and effectiveness of various herbal medicines for the treatment of respiratory symptoms.…”
contrasting
confidence: 63%
“…However, there are few studies on lung disease induced by PM. Although some animal model experimental studies conducted sporadically for respiratory diseases induced by PM have demonstrated the mechanisms and effectiveness of herbal medicine [17][18][19][20];…”
Section: Registration Numbermentioning
confidence: 99%
“…In addition, TBMS I has a strikingly anti-inflammatory effect on rheumatoid arthritis (RA); Bao et al (2018) and Liu et al (2018) discovered it represses the production of pro-inflammatory cytokines as well as downregulate the expression of MMP-9. Zhang et al (2018) ’s research shows that TBMS I ameliorates PM 2.5 -induced lung injury in mice; and the mechanism may be that it reduce the level of inflammatory cytokines, such as IL-1β, IL-6, IL-8, TNF-α, so as to improve PM 2.5 -induced lung injury by inhibiting inflammation. Wu et al (2013) utilize LPS-induced mice model of lung injury and LPS-stimulated RAW264.7 cells, and they found it remarkably inhibit the generation of pro-inflammatory cytokine (TNF-α, IL-6 and IL-1β) both in vivo and vitro.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…As results, treatment with TBMS1 attenuated the development of pulmonary injury. Its mechanisms of action were Soromou and Camara associated with reducing cytotoxic effects, levels of inflammatory mediators, and oxidative damage, indicating that TBMS1 is a potential therapeutic drug for treating lung injury [18]. In 2013, our laboratory investigated the protective effect of TBMS1 on inflammation in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells and a LPSinduced in vivo lung injury model.…”
Section: Anti-inflammatory Activity (Table 1)mentioning
confidence: 99%